Self Organization of Binary Colloidal Mixtures via Diffusiophoresis - Lei, Lijie; Wang, Shuo; Zhou, Xuemao; Ghellab, Salah Eddine; Lin, Guanhua; Gao, Yongxiang (Frontiers in Chemistry, 2022)
Catalytic activity of the colloids and a chemotactic response to gradients of the chemicals in the solution leads to an effective interaction between catalytic colloids. In this paper, We simulate mixtures of active and passive colloids via a Brownian dynamics algorithm. These particles interact via phoretic interactions, which are determined by two independent parameters, surface activity and surface mobility. We find rich dynamic structures by tuning passive colloids’ surface mobility, size and area fractions which include school of active colloids with exclusion zone, yolk/shell cluster, stable active-passive alloys to motile clusters. Dynamical cluster can also be formed due to the non-reciprocity of the phoretic interaction. Increasing the size ratio of passive colloids to active colloids favors the phase separation of active and passive colloids, resulting in yolk/shell structure. Increasing the area fraction of active colloids tends to transfer from dynamical clusters into stable alloys. The simulated binary active colloids systems exhibit intriguing nonequilibrium phenomena that mimic the dynamic organizations of active/passive systems.